Skeletal kinetic mechanism for diesel combustion. Issue 1 (2nd January 2017) - Frassoldati, Alessio; Cuoci, Alberto; Stagni, Alessandro; Faravelli, Tiziano; Ranzi, Eliseo
Abstract : In this work, a skeletal kinetic mechanism is obtained for the Integrated Development on Engine Action (IDEA) surrogate, i.e. a mixture of n -decane (ND) and α-methyl-naphthalene (MN), and comprehensively validated. The lumped POLIMI_TOT_1407 pyrolysis and oxidation mechanism of hydrocarbon and oxygenated fuels, containing 451 species and 17, 747 reactions, is reduced to a skeletal level, consisting of 123 species and 1017 reactions, through a combination of flux-based analysis (directed relation graph with error propagation) and sensitivity analyses on species and reactions. In this way, it is possible to remove unimportant species and reactions with an automatic control of the maximum error associated with the reduction. Several comparisons with experimental data for the two individual components of this surrogate and their mixtures are discussed in this paper and support the validation of the skeletal mechanism. The experimental data used in this paper refer to measurements of species concentration from flow and stirred reactors experiments, autoignition delay times, flame speed and autoignition of isolated fuel droplets in microgravity conditions. It is shown that, although the reduction procedure is targeted at the autoignition behaviour, a satisfactory agreement is observed in all the 0D and 1D case studies, thus laying the foundations for an extensive use in multidimensional computational fluid dynamics applications.